2018
DOI: 10.18203/2320-6012.ijrms20180297
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of conjunctival autograft with fibrin glue or glueless sutureless conjunctival autograft after pterygium surgery

Abstract: Background: Conjunctival autografting after Pterygium excision can be done by fibrin glue or sutures but use of foreign material can cause discomfort and infection. Fibrin glue may cause hypersensitivity reaction and also have risk of viral transmission. To avoid these conjuctival autograft can be applied without suture or glue. Patient’s own blood act as a bioadhesive.Methods: We done a prospective randomized control study of 70 patients, 35 patients allocated in each group. Group A had conjunctival autograft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…de Wit et al 30 described another technique of sutureless and glueless technique of conjunctival autograft in a case series and concluded that it provides good cosmesis and no post-operative complications. This technique of sutureless and glueless technique was used by Jain et al 31 which demonstrated the rate of recurrence of pterygium to be same in sutureless and glueless conjunctival autograft and conjunctival autograft with glue but graft displacement and retraction were more in the former group, thus making fibrin glue usage for securing conjunctival autograft a more safe technique. However, the main disadvantage of fibrin glue is its cost.…”
Section: Wwwdjoorgin Delhi Journal Of Ophthalmologymentioning
confidence: 99%
“…de Wit et al 30 described another technique of sutureless and glueless technique of conjunctival autograft in a case series and concluded that it provides good cosmesis and no post-operative complications. This technique of sutureless and glueless technique was used by Jain et al 31 which demonstrated the rate of recurrence of pterygium to be same in sutureless and glueless conjunctival autograft and conjunctival autograft with glue but graft displacement and retraction were more in the former group, thus making fibrin glue usage for securing conjunctival autograft a more safe technique. However, the main disadvantage of fibrin glue is its cost.…”
Section: Wwwdjoorgin Delhi Journal Of Ophthalmologymentioning
confidence: 99%